KEPUASAN KONSUMEN PENGGUNA SMARTPHONE ANDROID SAMSUNG MELALUI KUALITAS PRODUK, MEREK DAN HARGA DI KECAMATAN GROGOL KABUPATEN SUKOHARJO - Pera Setyaningsih; Nuryati . (STIE AUB Surakarta, 2016)
This study aimed to test the influence of the quality of the product, the brand and the price of consumer satisfaction against Samsung android smartphone users in the GrogolsubdistrictSukoharjo Regency. The population of this research is all Samsung android smartphone user Grogolsubdistrict relic in Sukoharjo Regency. The study sampled the Grogolsubdistrict community using Samsung android smartphone that add up to 100 people. The technique of sampling by means of Random Sampling.Based on multiple linear regression test results indicate that the variable quality of the product, the brand and the price effect is positive towards consumer satisfaction, variable pricing most dominant influence consumer satisfaction Samsung android smartphone users. The results of the test t variable product quality effect is not significantly to consumer satisfaction, brand and price influential variables significantly to consumer satisfaction. Based on the F-test of the variable quality of products, brands and price together influential significantly to consumer satisfaction android Samsung smartphone user Grogolsubdistrict relic in Sukoharjo Regency. Keyword: product quality, brand, price and customer satisfaction.